Numerical simulation of the motion of a wedge-shaped two-mass vibration-driven robot in a viscous fluid - Nuriev, Artem Nailevich; Zakharova, Olga Sergeevna (Computational Continuum Mechanics, 2016)
The translational motion of a two-mass mechanical system in a viscous incompressible fluid is considered. The system consists of a closed wedge-shaped body placed in a liquid and a movable internal mass oscillated harmonically inside the shell. The motion of the whole system is ensured by the periodic oscillations of the internal mass. The asymmetry in the shell shape generates different reactions of the fluid at different phases of motion (forward and backward), providing the directional translational motion of the system in the liquid. The described mechanical system simulates a vibration-driven robot - a mobile device able to move in the fluid without moving external parts. The problem of an interaction between the robot and the viscous fluid is solved using direct numerical simulation. Studies are carried out in a range of low Reynolds numbers (Re < 250), where the hypothesis of a plane-parallel laminar flow is applicable. A computational scheme is constructed on the basis of an open-source software package OpenFOAM. The results of this work show that the fluid-shell interaction is a complex phenomenon associated with switching between flow regimes. The flow structure formed by the robot motion has a strong influence on the characteristics of the movement, including the direction of the movement. Furthermore, the high nonlinearity of the processes leads to the formation of significantly different regimes of robot motion at the same parameters of internal mass oscillations.
Keywords: vibration-driven robot; numerical simulation; motion regimes; viscous fluid; Navier-Stokes equations; OpenFOAM